A geographical analysis of diversification in South Wales - Conkling, Edgar Clark 1921- (Evanston, Ill. Department of Geography, Northwestern University, 1962)
Thesis (Ph.D. Geography)--Northwestern University, 1962.
Keywords: Wales, South -- Economic conditions; Wales, South -- Industries